Patterns of Sexualized Drug Use among Gay, Bisexual, and Other Men Who Have Sex with Men Living with HIV: Insights from a Comprehensive Study¿The U-SEX-2 GESIDA 9416 Study - Ryan, Pablo; Dolengevich-Segal, Helen; Ramos-Ruperto, Luis; Cabello, Alfonso; Sánchez-Conde, Matilde; Vergas, Jorge; Valencia, Jorge; Cuevas, Guillermo; Sanz, José; Curto-Ramos, Javier; Pérez-Bootello, Javier; Naharro-Rodriguez, Jorge; et al. (MDPI, 2023)
: Background: Sexualized drug use (SDU) has become a public health concern in recent years. This study aimed to estimate the prevalence of SDU in gay, bisexual, and other men who have sex with men living with HIV (HIV + GBMSM) in Madrid during 2019/2020 and compare it with data from 2016/2017 in order to detect changes in patterns. Methods: We analyzed the frequency of SDU in a sample of HIV + GBMSM attending HIV clinics, who participated in an anonymous online survey regarding sexual behavior and recreational drug use. The association between SDU, sexual risk behaviors, and STIs was evaluated. Results: This study included 424 HIV + GBMSM, with a mean age of 40 (10.43) years. Overall, 94% (396) reported being sexually active. Additionally, 33% (140) had been diagnosed with an STI within the previous year. Moreover, 54% (229) had used drugs in the last year, 25% (107) engaged in SDU, and 16% (17) reported engagement in slamsex. After adjusting for confounding factors, SDU was associated with STIs, fisting, unprotected anal intercourse, and having >24 sexual partners in the last year. According to the DUDIT test scores, 80% (81) probably had problematic drug use (¿6 points), and 8% (8) probable drug dependence (¿25 points). When comparing the U-SEX-1 (2016/2017) data with the U-SEX-2 (2019/2020) data, no significant differences were found in the proportion of participants practicing SDU or slamming. Conclusions: The prevalence of SDU among HIV + GBMSM has remained high in recent years and without significant changes. The risk of problematic drug use among those who practice SDU is high. We observed a clear association between SDU, high-risk sexual behaviors, and STIs.